1992
DOI: 10.1289/ehp.9297241
|View full text |Cite
|
Sign up to set email alerts
|

Sequential respiratory, psychologic, and immunologic studies in relation to methyl isocyanate exposure over two years with model development.

Abstract: Of 113 methyl isocyanate (MIC)-exposed subjects studied initially at Bhopal, India, 79, 56, 68, and 87 were followed with clinical, lung function, radiographic, and immunologic tests at 3, 6, 12, 18, and 24 months. Though our cohort consisted of subjects at all ages showing a varied severity of initial illness, fewer females and young subjects were seen. Initially all had eye problems, but dominant symptoms were exertional dyspnea, cough, chest pain, sputum, and muscle weakness. A large number showed persisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…They did not attempt to correlate their findings with a measure of exposure. Kamat and colleagues followed 113 subjects who had been initially admitted to hospital 12. Over two years they found no improvement in respiratory symptoms or in basic spirometry, but 42% of the group had evidence consistent with deteriorating small airways function.…”
Section: Discussionmentioning
confidence: 99%
“…They did not attempt to correlate their findings with a measure of exposure. Kamat and colleagues followed 113 subjects who had been initially admitted to hospital 12. Over two years they found no improvement in respiratory symptoms or in basic spirometry, but 42% of the group had evidence consistent with deteriorating small airways function.…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of thousands of people were exposed to methyl isocyanate as a result of an accidental release in Bhopal, India in 1984. Long‐term follow‐up of this population was difficult, but some evidence was obtained for persistent effects, such as respiratory symptoms, lung function impairment (including both obstructive and restrictive changes), inflammation, and histological abnormalities (including airway inflammation and fibrosis) . Animal studies have shown long‐lasting effects of acute methyl isocyanate exposure on airway structure .…”
Section: Insights From Other Inhaled Toxicantsmentioning
confidence: 99%
“…It would thus appear that the lethal effects of MIC were caused by pulmonary complications. It was also found that a single exposure to MIC can produce long-lasting pulmonary complications (Ferguson and Alarie, 1991;Kamat et al, 1992;ICMR, 2004).…”
Section: Mechanism Of Death Following Exposure To Micmentioning
confidence: 99%
“…Since the prevalence of compromise in lung function was higher in the population closer to the Union Carbide plant than in the population farther away, it is very likely that this occurred as a result of exposure to the toxic gases rather than preexisting bronchitis, tuberculosis, or emphysema. A follow-up of 113 exposed patients revealed worsening of pulmonary symptoms 2 years later, forced expiratory flow (FEF) between FEF 25% and FEF 75% of forced vital declined progressively over a 2-year period (Kamat et al, 1985(Kamat et al, , 1992Patel et al, 1987), a 1-to 7-year period (Vijayan et al, 1989;Vijayan and Kuppurao, 1993;Vijayan and Sankaran, 1996) and a 10-year period (Acquilla et al, 1996;. Likewise, other researchers have found a direct relationship between pulmonary function compromise and inflammatory alveolitis and the severity of exposure (Vijayan et al, 1989).…”
Section: Pulmonary Complicationsmentioning
confidence: 99%